Emergency food distribution efforts in New Orleans, LA after Hurricane Ida - Singleton, Chelsea R.; Chaparro, M. Pia; O'Malley, Keelia; Fuster, Melissa; Rose, Donald (Frontiers in Public Health, 2022)
Background The provision of food aid after a natural disaster is necessary to prevent hunger, particularly in low-resourced and low-income communities. Little is known about the operational challenges associated with ensuring equitable distribution of emergency food resources to communities in need following a disaster. To address this gap, this study assessed emergency food distribution efforts in New Orleans, LA during the 2 weeks following Hurricane Ida's landfall on August 29, 2021. Methods Information on free food distribution events was gathered from online sources. A list of distribution sites was generated that included data on operational logistics (e.g., address, days of operation, hours of operation, etc.), food offerings (e.g., prepared meals, groceries, etc.), and socio-demographic characteristics of the surrounding community. Geospatial mapping and bivariate analyses were used to analyze the site data. Results Seventy-four distribution sites operated in the 2 weeks after Hurricane Ida. Approximately 47.3% were located in census tracts with >80% Black residents, and 39.2% were in tracts with >30% poverty. A large proportion of sites offered prepared meals (86.2%) and only operated 1 day (36.5%). Tracts with >80% Black residents had more sites that operated only 1 day (p = 0.04). Tracts with >30% poverty had more sites that started distributing food resources 7–15 days after the hurricane (p = 0.02). Conclusions Most low-income and low-resourced communities in New Orleans had access to emergency food resources; however, several limitations in operations were identified that may have influenced access. Future initiatives to prevent hunger after a natural disaster in New Orleans, and elsewhere, should improve operational logistics for food aid.